The effect of dietary chitin on growth and nutrient digestibility in farmed Atlantic cod, Atlantic salmon and Atlantic halibut. (3rd August 2015) - Karlsen, Ørjan; Amlund, Heidi; Berg, Arne; Olsen, Rolf Erik
Abstract: The effect of adding 0%, 1%, 2% and 5% chitin from prawn shells in the diets for Atlantic cod, Atlantic halibut and Atlantic salmon on growth was investigated. Nutrient digestibility and feed utilization was investigated in salmon and cod. Atlantic cod grew from 186 ± 29 to 383 ± 78 g ( N  = 960) over 13 weeks. Dietary chitin had no effect on length, weight, condition, liver size or specific growth rate (SGR). The apparent digestibility (ADC) for protein ranged from 84.7% to 86.5%, lipid between 88.8% and 93.1% and dry matter from 96.1% to 96.6%. Feed utilization varied between 1.08 and 1.11 and was not correlated with dietary chitin content. Atlantic salmon tripled their weight from 199 ± 9 to 615 ± 75 g ( N  = 480) during the 13 weeks. High inclusions of chitin (>1%) reduced both growth rate and condition. Protein and lipid ADC was negatively correlated with dietary chitin. Feed utilization ranged between 0.86 and 0.90 and was not significantly affected by dietary chitin. Faecal protein increased significantly with increasing dietary chitin, while faecal dry matter and lipid did not. Individually tagged Atlantic halibut grew from 1300 ± 470 to 2061 ± 714 g ( N  = 70) during 6 months. Individual growth rates varied within each group from being slightly negative to 0.81%·day −1 . Diet had no significant effect on growth rates. Atlantic cod and Atlantic halibut seems unaffected by up to 5% chitin additions in the diet, while chitin >1% of diet negatively affects growth and nutrient utilization in Atlantic salmon.